Performance development & training : with Asian perspectives - Osman-Gani, Aahad M. (McGraw-Hill Publishers, 2006)
This book is designed as a supplement to other major texts (such as Ray Noe's Employee Training & Development) to enable the students Wlderstand the theories, frameworks and conceptual underpinnings of learning, training & development, and to apply the modem HRD tools and techniques in addressing the performance development issues, particularly in the Asian context. The book may also help in developing the management thinking on how T&DIHRD can play significant strategic roles in managing people. The contents will provide guidelines in the needs assessment, design, delivery and evaluation of training programs in organizations. Technological developments in T&D and E-learning issues are also be emphasized. The book covers various topics focusing on strategic as well as operative issues of learning and performance development of employees in dynamic organizations. Additional research articles on training and performance development in the Asia-Pacific context have alsovbeen included, to provide the readers with first hand knowledge on the empirical findings in this area